Efektifitas Penggunaan Media Pembelajaran Wordbrain Game Untuk Meningkatkan Penguasaan Kosa Kata Bahasa Inggris - Musmuliadi, Musmuliadi (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2024)
This study is carried out to find out the effectiveness of applying wordbrain game as learning media to improve students vocabulary mastery in english. This study used quasy experimental recearch with nonequivalent pre test pos test control group design. The population of this study was the second year student of smpn 5 sikur in academic year 2023/2024. The samples are divided in two groups, experimental group and control group. The data of this study is collected by applying 3 steps those are pretest, treatment and post-test of vocabulary. Pretest and posttest are used to find out whether wordbrain can be used to improve students’ vocabulary mastery in English. In analyzing data, the researcher used statistical procedures (mean score test, gain score test and T-test formula for test result). Based on the data analysis T-test result, it is showed that the value of T-test is higher than T-table which means that T-test value is significant. According the data, it can be conlcluded tha the use off wordbrain as learning media to improve student vocabulary masteri in english  is efective siginficantly.